The Influence of Persuasive Communication on the Success of B2B Sales - Cunha, Ana Flávia Brugnara (Revista JRG de Estudos Acadêmicos, 2025)
Persuasive communication is one of the cornerstones of performance in business-to-business (B2B) sales, given the complexity of organizational decision-making processes, which involve multiple stakeholders, high investments, and long purchasing cycles. This literature review aimed to critically analyze the influence of persuasive communication on the success of B2B sales, integrating theoretical foundations and empirical evidence published between 2010 and 2025 in databases such as Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, and SciELO. A total of 32 studies were selected and analyzed using the SALSA framework (Search, AppraisaL, Synthesis and Analysis). The findings indicate that classical persuasion models, such as the Elaboration Likelihood Model (ELM), the Heuristic-Systematic Model (HSM), and the Persuasion Knowledge Model (PKM), provide valuable insights into how messages are processed in B2B contexts. Moreover, the use of adaptive influence tactics, combined with adaptive selling and sales communication competence, proved crucial for value co-creation and trust building in commercial relationships. The literature also emphasizes that interorganizational communication quality is essential for satisfaction, partnership continuity, and strategic customer loyalty. On the other hand, gaps were identified, such as the lack of longitudinal studies, the need to consider cultural differences, and the ethical implications of persuasion strategies in sales. It is concluded that persuasive communication, when applied ethically and strategically, represents not only an immediate competitive advantage but also a driver of sustainability in B2B relationships, while opening avenues for future research on the impact of digitalization on persuasive processes.